2019
DOI: 10.1016/j.addbeh.2018.10.020
|View full text |Cite
|
Sign up to set email alerts
|

Substance use disorders and PTSD: Examining substance use, PTSD symptoms, and dropout following imaginal exposure

Abstract: Integrated exposure-based interventions to treat substance use disorders (SUD) and posttraumatic stress disorder (PTSD) may not be widely utilized, in part, because of clinician concerns that such interventions will worsen symptomatology and lead to treatment dropout. In order to address this question, the current pilot study examined whether participants’ ratings of craving and distress following imaginal exposure predicted increased substance use, PTSD severity, and treatment dropout. Participants (N=46) wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 41 publications
4
11
0
Order By: Relevance
“…Moreover, neither substance craving nor substance use increased over baseline levels in any week of treatment regardless of exposure content. Overall, craving levels were fairly low and similar to those reported in other studies (Jarnecke et al., 2019). Active substance use was common and similar to what has been reported in other samples of patients with PTSD receiving methadone (e.g., Trafton, Minkel, and Humphreys, 2006), although somewhat higher than other studies of SUD patients who were offered exposure‐based therapy (Back et al., 2019).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Moreover, neither substance craving nor substance use increased over baseline levels in any week of treatment regardless of exposure content. Overall, craving levels were fairly low and similar to those reported in other studies (Jarnecke et al., 2019). Active substance use was common and similar to what has been reported in other samples of patients with PTSD receiving methadone (e.g., Trafton, Minkel, and Humphreys, 2006), although somewhat higher than other studies of SUD patients who were offered exposure‐based therapy (Back et al., 2019).…”
Section: Discussionsupporting
confidence: 89%
“…The lack of an association between PTSD severity and subsequent substance use is consistent with studies documenting similar rates and severity of substance use in SUD samples with and without PTSD (Dworkin, Kaysen, Bedard-Gilligan, Rhew, & Lee, 2017;Peirce, Brooner, Kolodner, Schacht, & Kidorf, 2013;Peirce et al, 2016), but contrary to what has been reported in some prospective studies (e.g., Black, Cooney, Sartor, Arias, & Rosen, 2018;Dworkin et al, 2017;Hien et al, 2010). In contrast, self-reported substance use in the present study was moderately associated with more severe PTSD symptoms, which has also been documented in recent studies of exposure-based therapy (Hien et al 2018;Jarnecke et al, 2019). Helping patients reduce or eliminate substance use might have more benefit on their PTSD symptoms than has previously been understood.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Participants completed a large assessment battery. 4 Measures relevant to the present study included the Mini International Neuropsyhiatric Interview (baseline), the Clinician Administered PTSD Scale (baseline and last session), the PTSD Symptom Checklist (baseline 1 For a full report of the overall outcomes from this randomized clinical trial, see additional publications (Back et al, 2019;Jarnecke et al, 2019). The 2:1 randomization ratio was used due to ethical concerns.…”
Section: Methodsmentioning
confidence: 99%
“…Coping mechanisms are considered any adjustment or change in behavior that decreases tension and anxiety in a stressful situation (American Psychological Association [APA], 2020). Recent research has identified that veterans diagnosed with PTSD frequently use licit and/or illicit substances to cope (Banducci et al, 2019;Jarnecke et al, 2019;Silins et al, 2016). A Canadian study found that male veterans from regular and reserve duty forces of the military and diagnosed with PTSD scored higher on a measure of alcohol use disorders compared to those with subthreshold or no PTSD (Fetzner et al, 2013).…”
mentioning
confidence: 99%